The perceptions of the School Management Teams towards the effectiveness of the new management system within Malamulele West Circuit of Limpopo Province - Baloyi, Masenyani Joseph (My University, 2011)
The functioning of the school within the new education dispensation has brought about radical changes in the management of schools where the formation of school management teams (SMTs) became a necessity in order to assist principals in the day to day management of schools so that effective, proper management can be applied. The introduction of the New Management System compelled the heads of institutions and all other relevant stakeholders to undergo comprehensive management training in order to contribute towards the management of schools. However, very little has been done to evaluate the perceptions of people who have to implement the new management system as to whether it is working or not. This study was aimed at finding out the perceptions of the School Management Teams (SMTs) and School Principals towards the effectiveness of the new management system within the Malamulele West Circuit of the Limpopo Province. The study also intended to explore the gap existing between schools management policy and the way it is understood and implemented by the School Management Teams in schools. The study utilized a questionnaire as an instrument of collecting data. Interviews were arranged with the respondents and they were interviewed following the standardized questionnaire. The findings show that School Management Teams did not feel effective in managing schools using the new management system. The SMTs did not have confidence in implementing the strategic management plans and practicing management effectively. The School Management Teams recommended amongst others, that they be sent for training. They envisaged that training programmes would assist School Management Teams in developing the competencies they need to perform their best in their current jobs. The study has also revealed that both School Management Teams and School \principals feel that they are not properly trained in management skills.
Thesis (MBA.) -- University of Limpopo, 2011
Keywords: School management teams; Educational leadership; School management and organization -- South Africa -- Limpopo; School management teams; Educational leadership; School proncipals